Legal Protection for Midwives Performing Medical Procedures at Tanjung Enim Community Health Center - Yopi Puspasari; Yuyut Prayuti (Jurnal Iman dan Spiritualitas, 2026)
Midwives, as health workers, play a crucial role in the provision of maternal and child health services, particularly at Community Health Centers (Puskesmas) as primary healthcare facilities. In their practice, midwives often face potential legal risks, particularly when medical procedures are deemed to exceed their authority or cause harm to patients. This situation places legal protection as a crucial aspect in ensuring professional safety while maintaining the quality of healthcare services. This study aims to analyze the forms of legal protection for midwives in the implementation of medical procedures at the Tanjung Enim Community Health Center and to examine the legal responsibilities that may arise in the event of errors or negligence in the service. The research method used is a mixed approach: normative legal research by examining laws and regulations related to midwifery practice and healthcare services, and empirical research through in-depth interviews with two midwives and the Head of the Tanjung Enim Community Health Center. The data obtained were analyzed to assess the conformity between normative provisions and field practice. The results indicate that preventive legal protection is available through the implementation of Standard Operating Procedures (SOPs), competency improvement training, regulation of authority by the Indonesian Health Workforce Council, and the implementation of informed consent before medical procedures. In addition, repressive protection is also available in the form of administrative clarification mechanisms and assistance from Community Health Centers (Puskesmas) and the Health Office in the event of a complaint. However, midwives' understanding of the legal aspects remains limited, and medical documentation is suboptimal, creating a gap between regulation and implementation. Therefore, strengthening legal literacy, improving the quality of medical records, and developing more comprehensive legal assistance guidelines are needed to ensure legal certainty and the safety of the midwifery profession.